Evaluation of the Effectiveness of Millettia pachyloba drake Leaf Ethanol Extract in Alleviating Oxidative Stress Induced by Diamondback Moth Infestation in Mustard Greens [Brassica juncea (L.) czern. & coss.] - Nhung Tran Thi Phuong; Quoc Le Pham Tan (Journal of Horticultural Research, 2024)
The global threat that the diamondback moth (DBM) (Plutella xylostella) poses to Brassica juncea creates an urgent need to develop effective mitigation strategies. With promising findings, this study explores the potential of plant-derived antioxidants, particularly Millettia pachyloba, in mitigating DBM-induced oxidative stress. Greenhouse experiments conducted using M. pachyloba leaf ethanol extract (MPEE) at concentrations of 2, 4, 6, 8, and 10 % (w/v) showed the inhibitory effect of MPEE on DBM damage in B. juncea. The comprehensive assessment included the effectiveness of MPEE in reducing oxidative stress markers (malondialdehyde, hydrogen peroxide), augmenting metabolites (flavonoids, phenolics), enhancing anti-oxidant compounds (glutathione, ascorbic acid, total protein), and stimulating key enzymes (su-peroxide dismutase, catalase, and ascorbate peroxidase). The results were compared to controls, in which the plants were treated with water or fipronil. Fipronil and MPEE significantly reduced leaf puncturing and damage, and the impact force increased with MPEE concentration. Both types of protection reduced the content of malondialdehyde and hydrogen peroxide in leaves, stems, and roots. However, a significant increase in the content of flavonoids, phenolic and antioxidant compounds (glutathione, ascorbic acid, and proteins) and enzyme activity (superoxide dismutase, ascorbate peroxidase, and catalase) was observed. The enhancement of metabolites, enzymes, and antioxidants was comparable in plants treated with fipronil and MPEE 10%. This study, with its potential to replace synthetic fipronil with M. pachyloba extracts to reduce oxidative stress induced by Plutella xylostella on mustard plants, offers a promising solution for protection against this insect.